Screening of the strawberry collection for the presence of resistance loci Rca2 and 08 To-f - A. V. Khudyakova; M. G. Markova (Аграрная наука Евро-Северо-Востока, 2025)
Garden strawberry (Fragaria × ananassa Duch.) is one of the most common cultivated berry crops. Fungal diseases cause enormous damage to industrial plantings. The main task of modern breeding is to create strawberry cultivars with genetic determinants of resistance to various pathogens. The aim of the research was to identify the resistance loci of Russian and foreign strawberry cultivars to anthracnose (Rca2) and powdery mildew (08 To-f) using DNA markers. The objects of the study were 32 strawberry cultivars from the Udmurt Federal Research Center of the Ural Branch of the Russian Academy of Sciences collection, including 21 samples of Russian strawberry cultivars and 11 of foreign breeding. The dominant diagnostic DNA markers STS-Rca2_240 and IB535110 were used to identify the resistance genes of the strawberry. PCR monitoring was performed using the EMFv020 marker. As a result of molecular genetic screening, the anthracnose resistance gene Rca2 was detected in one Russian strawberry cultivar (‘Krasnaya pchelka’, Russia) and in one foreign cultivar (‘Malling Pandora’, Great Britain). QTL 08 To-f was detected in four cultivars of the collection: one Russian strawberry cultivar (‘Duet’) and three foreign cultivars (‘Malwina’, Germany; ‘Marmion’, Scotland; ‘Malling Pandora’). In total, among the analyzed strawberry genotypes, marker STS-Rca2_240 was detected in 6.3 % of the studied forms, and the marker IB535110 in 12.5 %. The complex source of Rca2 and QTL 08 To-f resistance alleles was only the ‘Malling Pandora’ cultivar. The identified promising genetic sources will be used in the breeding program for producing of fungal pathogens resistant garden strawberry cultivars.